Africanization and Centralization: Roman Strategies in Sub-Saharan Africa in the Late Colonial Period (1930s-1950s) - (:unkn) unknown (My University, 2022)
After World War I, missionary strategies in Sub-Saharan Africa were deeply renewed. Rome claimed authority over missionary organization, promoted an Africanization of the clergy and sought to lead the missions to emancipate themselves from European powers. These evolutions weren’t translated into concrete action until the 1930s, and accelerated spectacularly in the 1950s, on the eve of independence.
Keywords: African Research